Dietary Diversity and Self-Reported Memory Deterioration in Chinese Adults: A Prospective Study. (29th May 2020) - Zhang, Jian; Zhao, Ai; Yang, Chenlu; Ren, Zhongxia; Wu, Wei; Wang, Meichen; Wang, Peiyu; Zhang, Yumei
Abstract: Objectives: To investigate the association between dietary diversity and memory deterioration in Chinese adults aged 50 years or older. Methods: This study was based on the China Health and Nutrition Survey, a longitudinal study initiated in 1989. Information on general characteristics, lifestyle behaviors, medical history, and dietary intake (by 3-day dietary recall and household food inventory) were collected in each survey round. In the survey 2015, participants were additionally asked "How is your memory?" (very good, good, OK, bad, or very bad) and "In the past twelve months, how has your memory changed?" (improved, stayed the same, or deteriorated). The dietary diversity score (DDS) was developed according to the Chinese Dietary Guidelines and was calculated based on the data collected in the survey 2011. The DDS included eight food groups (cereals and tubers, vegetables, fruits, meat, soybeans and nuts, eggs, aquatic products, and milk and dairy products). If a participant consumed any food from a certain food group in the past 24 hours, then he would get one point for that food group. Average daily DDS scores were calculated. Participants who had been diagnosed with apoplexy and those who were uncertain about their memory status were excluded. Multinomial Logistic regression models were conducted to investigate the association between DDS scores and self-reported memory changes, taking the participants whose memory stayed the same as the reference. In the multivariate analysis, covariates (age, gender, residential region, education, and alcohol consumption) were adjusted. Results: Of the 4363 participants included in our analysis, the percentages of participants who thought their memory was OK, bad (bad or very bad), and good (good or very good) were 43.3%, 24.3%, and 32.4%, respectively. 47.3% of the participants reported memory deterioration in the past 12 months, and 1.4% reported memory improvement. The average value of DDS in participants was 4.09 ± 1.13. Multivariate analysis showed that higher DDS (OR = 0.82, 95% CI = 0.77∼0.87, P  < 0.001) was inversely associated with the risk of memory deterioration. No association between memory improvement and dietary diversity was observed. Conclusions: Lower dietary diversity was associated with self-reported memory deterioration in Chinese adults. Funding Sources: The authors received no financial support.